RESILIENCE OF RISK SEXUAL BEHAVIOR BASED ON SEX IN THE JUNIOR HIGH SCHOOL IN SEMARANG CENTRAL JAVA - Rakhmawati, Dini; Nurihsan, Juntika; Suherman, Uman (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
Resilience refers to the pattern of positive adaptation in the face of risk or difficulty (Masten & Coatsworth, 1998; in Luthar, 2003). Adolescents who have experienced less favorable conditions risk factors tend to be more susceptible to irregularities and problem behaviors including risky sexual behavior, but there are also teenagers who have resilience in the face of adversity. Patterns teens are able to survive and recover effectively called resilience. Teens who have high resilience, will have the possibility to grow faster and happier than teens who do not have or lack the ability to bounce back from adversity (Reivich & Shatte, 2002). The basic assumption in the study of resilience is that some individuals remain fine even though it has experienced a situation laden adversity and risky, while some other individuals fail to adapt and mired in adversity or risk a heavier again (Schoon, 2006). Low levels of resilience in adolescents will lead to vulnerability to the risks of adversity that lead to high-risk sexual behavior.Biological development, including gender, personal characteristics of adolescents, the situation in schools, peers, and family is something that has two sides, five things can serve as a protective factor may also be a risk factor for the development of adolescent resilience against risky sexual behavior. When adolescents can not face the risk factors that occur in the next life will result in the occurrence of risky behaviors such as risky sexual behavior.